Three-Dimensional In Vitro Models of Granuloma to Study Bacteria-Host Interactions, Drug-Susceptibility, and Resuscitation of Dormant Mycobacteria. (21st May 2014) - Fitzgerald, Liam E.; Abendaño, Naiara; Juste, Ramon A.; Alonso-Hearn, Marta
Abstract : Mycobacterium tuberculosis, Mycobacterium leprae, Mycobacterium bovis, and Mycobacterium avium subsp. paratuberculosis can survive within host macrophages in a dormant state, encased within an organized aggregate of immune host cells called granuloma. Granulomas consist of uninfected macrophages, foamy macrophages, epithelioid cells, and T lymphocytes accumulated around infected macrophages. Within granulomas, activated macrophages can fuse to form multinucleated giant cells, also called giant Langhans cells. A rim of T lymphocytes surrounds the core, and a tight coat of fibroblast closes the structure. Several in vivo models have been used to study granuloma's structure and function, but recently developed in vitro models of granuloma show potential for closer observation of the early stages of host's responses to live mycobacteria. This paper reviews culture conditions that resulted in three-dimensional granulomas, formed by the adhesion of cell populations in peripheral blood mononuclear cells infected with mycobacteria. The similarities of these models to granulomas encountered in clinical specimens include cellular composition, granulomas' cytokine production, and cell surface antigens. A reliable in vitro dormancy model may serve as a useful platform to test whether drug candidates can kill dormant mycobacteria. Novel drugs that target dormancy-specific pathways may shorten the current long, difficult treatments necessary to cure mycobacterial diseases.